Nuclear factor-kappa B subunits and their prognostic cancer-specific survival value in renal cell carcinoma patients - Ng, Keng Lim; Yap, Ning Yi; Rajandram, Retnagowri; Small, David; Jayalakshmi, Pailoor; Ong, Teng Aik; Razack, Azad Hassan Abdul; Wood, Simon Thomas; Morais, Christudas; Gobe, Glenda Carolyn (Lippincott Williams & Wilkins, 2018)
Better characterisation and understanding of renal cell carcinoma (RCC) development and progression lead to better diagnosis and clinical outcomes. In this study, expression of nuclear factor-kappa B (NF-κB) subunits: p65 (RelA), p105/p50, p100/p52, and cRel in RCC tissue were compared with corresponding normal kidney, along with tumour characteristics and survival outcome. Ninety-six cases of RCC with paired normal kidney were analysed. Clinicopathological data, demographics and survival data were available. Immunohistochemistry (IHC) for NF-κB subtypes was analysed using the Aperio digital pathology system for overall cellular expression and localisation. The prognostic cancer-specific survival value of the subunits in RCC patients was analysed. Approximately 50% of patients had clinical stage T1, with 22 patients having metastases at presentation. RCC subtypes were: clear cell (n = 76); papillary (n = 11); chromophobe (n = 5); clear cell tubulopapillary (n = 3); and one multilocular cystic RCC. Median follow up was 54.5 months (0.2–135), with 28 deaths at time of analysis. NF-κB p65 had higher overall and nuclear expressions, with lower overall and nuclear expressions of p50, p52 and cRel in RCC compared with normal kidney. Higher expressions of p65 (nuclear), p52 (overall and nuclear) and p50 (overall) correlated significantly with worse cancer-specific survival. This is the first large series of analysis of expression of NF-κB subunits in RCC. Especially with regards to the less studied subunits (p52, p50, cRel), our results allow a better understanding the role of NF-κB in RCC development and progression, and may pave the way for future targeted NF-κB subunit specific therapies.